2021
DOI: 10.48550/arxiv.2103.03888
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The bursty origin of the Milky Way thick disc

Sijie Yu,
James S. Bullock,
Courtney Klein
et al.

Abstract: We investigate thin and thick stellar disc formation in Milky-Way-mass galaxies using twelve FIRE-2 cosmological zoom-in simulations. All simulated galaxies experience an early period of bursty star formation that transitions to a late-time steady phase of near-constant star formation. Stars formed during the late-time steady phase have more circular orbits and thindisc-like morphology at 𝑧 = 0, whilst stars born during the bursty phase have more radial orbits and thick-disc structure. The median age of thick… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 8 publications
(21 citation statements)
references
References 34 publications
2
19
0
Order By: Relevance
“…Objects that are considered phase-mixed by the local velocity dispersion criterion are shown with orange error bars, while streams that pass the local velocity dispersion criterion are shown with blue error bars. The shaded region corresponds to the span in the end of the star formation bursty phase/onset of the steady phase in all the hosts, determined in Yu et al (2021), with the median value represented by the black vertical line. In the FIRE simulations, MW-mass galaxies generically have highly time-variable star formation histories at early times but eventually transition to more steady star formation rates after the disk settles (e.g.…”
Section: Validating the Local Velocity Dispersion Criterionmentioning
confidence: 99%
“…Objects that are considered phase-mixed by the local velocity dispersion criterion are shown with orange error bars, while streams that pass the local velocity dispersion criterion are shown with blue error bars. The shaded region corresponds to the span in the end of the star formation bursty phase/onset of the steady phase in all the hosts, determined in Yu et al (2021), with the median value represented by the black vertical line. In the FIRE simulations, MW-mass galaxies generically have highly time-variable star formation histories at early times but eventually transition to more steady star formation rates after the disk settles (e.g.…”
Section: Validating the Local Velocity Dispersion Criterionmentioning
confidence: 99%
“…Yoachim & Dalcanton 2006;Bovy et al 2012;Belokurov et al 2020;Agertz et al 2021;Park et al 2021), it is straightforward to make an internal comparison between the dwarf stellar outskirts and massive thick disks within the context of the FIRE-2 simulations. It has been demonstrated that the thickened shape of the thick disks in the more massive FIRE-2 galaxies is due to an inherently broader configuration of star formation during a bursty phase of star formation at lookback times of t lb 5 Gyr (Yu et al 2021). It is thus of interest to examine whether the shape of the FIRE-2 dwarf stellar populations are set by stellar migration or by a change in the star formation configuration as a function of cosmic time.…”
Section: The Origin Of Dwarf Halo Starsmentioning
confidence: 99%
“…We first consider the massive FIRE-2 galaxy; Figure 6 demonstrates that the star particles in this galaxy show a negligible change in vertical scale height between z = z form and z = 0. We exclude star particles with ages greater than 10 Gyr for the massive galaxy in this figure, as these stars are expected to be dominated by ex-situ stars (see Figure 5) and the majority of the massive FIRE-2 thick disks are assembled at times more recent than 10 Gyr (Yu et al 2021). This lack of scale height evolution is consistent with the results of Yu et al (2021), who find that the thick disks in these massive galaxies are formed as thick disks from birth, rather than from stellar displacement after formation.…”
Section: The Origin Of Dwarf Halo Starsmentioning
confidence: 99%
See 2 more Smart Citations